A new paradigm for Political Studies: competence-based teaching and learning - Terrie R. Groth (Universidad de Deusto, 2015)
For some decades, students and scholars of Political Science have debated methodological differences, paradigmatic differences, and policy differences as they relate to curricula. Today, the real challenges facing the teaching of Political Science have less to do with content and much more to do with form and process. The next transformation in teaching and learning must address what kind of political scientist we wish to be, which kind of Political Science we need to create. Our argument advances in three moments. First, we sketch contemporary contexts for analyzing teaching and learning, musing about old and new paradigmatic/methodological debates and the new social-technological contexts of undergraduate learning. Second, we discuss conceptions of competencies in the U.S., Europe, and in relation to a specific Political Science program in Brazil. Third, we dare to sketch a "metaprofile" of the "good political scientist", modeled on the work of the ALFA Tuning Project of the European Commission and reflections on related Brazilian and Latin American experiences.